Generational characteristics of general medicine students in Iran - Azarmidokht Firoozjahantighi; Fariba jokar; Fariba Haghani; Shirin Ahmadnia (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Purpose: The success of any educational system depends on the fitness of the curriculum components with the characteristics of its audience. The students of the present generation are different from the previous ones due to the changes resulting from the changes that have taken place in society, media, technology, and communication as we entered the 21th century. Hence, this study was conducted to identify the characteristics of MD students in universities of medical sciences in Iran. MATERIALS AND METHODS: This qualitative study was conducted on 32 MD students among 7 universities of medical universities of Iran. The participants were selected through purposive sampling method, and the data were collected via semi-structured interviews after getting informed consent. Then, the data were analyzed using conventional content analysis method. RESULTS: Technology as a Double-Edged Sword, in digital age, Quick access, Reasoning the basis of acceptance. Evaluation ambiguity, Seeking independence,get involved in problems, desirable teaching qualities, my favorite teacher, features of content, Role models traces,my favorite teacher, The rest are unchanged. CONCLUSION: MD students are interested in using various teaching methods and technologies, applying methods that are similar to their future job and learning by doing; they also tend to use visual materials and shortening the time and memorizing content. They prefer professors who love to teach and are good role models for them. What motivates them is to be involved in the classroom, to be active, to be respected, and not to be ignored.